Noise reduction in synchrotron radiation phase-contrast mammography images - Ruíz González, Yusely; Brizuela Cardoso, Javier David; Pérez Díaz, Marlen (My University, 2019)
Phase contrast mammography using synchrotron beams (PCI_SR) has shown quantitatively better results in terms of image contrast and detection of small details with respect to conventional hospital digital techniques. However, this new technique shows higher levels of random noise than common digital techniques. The objective of this work was to reduce noise in PCI_SR images to levels similar to those of hospital equipment without significant affect the spatial resolution, contrast and visibility of fine details. Five filter, Wiener, Gauss, bilateral and wavelets families coif y biord were used and the image quality before and after filter process estimated by objective indicator. The results showed increases in Signal to Noise Ratio (SNR) without impairing other indexes used; which demonstrates the superiority in image quality of this innovative technique for the detection of small lesions such as microcalcifications and low contrast masses.
Keywords: Phase contrast mammography, digital filter, image quality